2017
DOI: 10.1038/ncomms13964
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA zippers lock miRNA molecules and block miRNA function in mammalian cells

Abstract: MicroRNAs (miRNAs) loss-of-function phenotypes are mainly induced by chemically modified antisense oligonucleotides. Here we develop an alternative inhibitor for miRNAs, termed ‘small RNA zipper'. It is designed to connect miRNA molecules end to end, forming a DNA–RNA duplex through a complementary interaction with high affinity, high specificity and high stability. Two miRNAs, miR-221 and miR-17, are tested in human breast cancer cell lines, demonstrating the 70∼90% knockdown of miRNA levels by 30–50 nM small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Therefore, the decrease of miRNA-122 levels in the experiments where molecular sponges were transfected demonstrates functional sequestration. Similar effects on miRNA levels detected by RT-qPCR were recently reported for sequestration of miRNA-17 and -221 by small RNA zippers [ 26 ].…”
supporting
confidence: 84%
“…Therefore, the decrease of miRNA-122 levels in the experiments where molecular sponges were transfected demonstrates functional sequestration. Similar effects on miRNA levels detected by RT-qPCR were recently reported for sequestration of miRNA-17 and -221 by small RNA zippers [ 26 ].…”
supporting
confidence: 84%
“…There are two types of miRNA targets: mRNAs with near perfect complementarity to the miRNA and mRNAs with limited complementarity to the miRNA [6,7]. miRNAs function in diverse physiological processes and an increasing number of studies have proven that miRNAs play vital roles in carcinogenesis by regulating gene expression through mechanisms including deletion, amplification, mutation of miRNA locus, and epigenetic silencing of miR-RNA target genes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that B-cell chronic lymphocytic leukemia (B-CLL) cell viability is gradually decreased over time after the inhibition of miR-222; they showed that the viability of LNA-anti-miR222–transfected cells was <47% of untreated cells at 72 h post-transfection. A small LNA, termed small RNA zipper, has been developed to inhibit miRNA by generating a DNA–RNA duplex through a complementary interaction with high affinity, specificity, and stability [ 69 ]. The small RNA zipper is a small LNA in which half of its sequence is complementary to the 5′-end of the target miRNA, and the other half is complementary to the 3′-end.…”
Section: Oncomir-targeting Strategiesmentioning
confidence: 99%
“…The small RNA zipper is a small LNA in which half of its sequence is complementary to the 5′-end of the target miRNA, and the other half is complementary to the 3′-end. All individual mature miRNAs can be connected end to end via the small RNA zipper following the zipper strategy ( Figure 3 ) [ 69 ]. For targeting miR-221 and miR-17, a concentration of 30–50 nM of small RNA zippers achieves a 70–90% knockdown of miRNA in human breast cancer cell lines [ 69 ].…”
Section: Oncomir-targeting Strategiesmentioning
confidence: 99%